6. \( 25\left(125^{-x}\right)=625 \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the equation \( 25\left(125^{-x}\right)=625 \), we can start by rewriting each term as a power of 5. We know that: - \( 25 = 5^2 \) - \( 125 = 5^3 \) - \( 625 = 5^4 \) Substituting these values into the equation gives us: \[ 5^2 \left( (5^3)^{-x} \right) = 5^4 \] This simplifies to: \[ 5^2 \left( 5^{-3x} \right) = 5^4 \] Combining the powers of 5 on the left side: \[ 5^{2 - 3x} = 5^4 \] Since the bases are the same, we can set the exponents equal to each other: \[ 2 - 3x = 4 \] Now, solving for \( x \): \[ -3x = 4 - 2 \] \[ -3x = 2 \] \[ x = -\frac{2}{3} \] Thus, the solution is \( x = -\frac{2}{3} \).